2010
DOI: 10.1007/s00265-010-0938-8
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in nest defense in the colonial breeding Black-tailed Gulls

Abstract: Often in colonial seabirds, all colony members are believed to defend against nest predators and experience equal nest predation risk. However, the variation of defense behavior among members and its reproductive consequences are largely unknown. We investigated 1) individual variation in the nest defense of breeding Black-tailed Gulls Larus crassirostris against a natural egg predator, the Jungle Crow Corvus macrorhynchos, and 2) how this behavioral variation affects an individual's own nest predation risk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…), these are almost exclusively at‐sea measures, where our understanding and ability to quantify the conditions experienced by individuals is poor. This study is one of the first that has measured consistent behavior in seabirds under relatively controlled conditions (but see Kazama and Watanuki ; Kazama et al. ) and these estimates of boldness could now be linked to at‐sea measures of consistent behavior.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…), these are almost exclusively at‐sea measures, where our understanding and ability to quantify the conditions experienced by individuals is poor. This study is one of the first that has measured consistent behavior in seabirds under relatively controlled conditions (but see Kazama and Watanuki ; Kazama et al. ) and these estimates of boldness could now be linked to at‐sea measures of consistent behavior.…”
Section: Discussionmentioning
confidence: 93%
“…While there are many studies examining consistent individual behavior in seabirds (e.g., Bearhop et al 2006;Jaeger et al 2010;Reviewed by Patrick et al in press), these are almost exclusively at-sea measures, where our understanding and ability to quantify the conditions experienced by individuals is poor. This study is one of the first that has measured consistent behavior in seabirds under relatively controlled conditions (but see Kazama and Watanuki 2010;Kazama et al 2012) and these estimates of boldness could now be linked to at-sea measures of consistent behavior. Individuals vary in their association with fisheries (Votier et al 2010;Torres et al 2011;Granadeiro et al 2013Granadeiro et al , 2011 and the distance they forage from the colony (Reviewed by Patrick et al in press), both of which are thought to be linked to competitive ability, and as such boldness may predict an individual's foraging strategy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Alternatively animals can engage in group defence. This can take two forms: indirect group defences such as aggressive displays or direct group defence such as body striking or swooping (Clode et al ., ; Kazama & Watanuki, ). Group defence effectiveness is increased in larger colony sizes due to the larger number of individuals contributing to defence (Krams, Bērziņš & Krama, ).…”
Section: Information For Predator Defencementioning
confidence: 98%
“…While in the past it has been assumed that individuals in a targeted area will contribute equally to group defence due to shared predation risk, it has been shown that different colony members adopt different strategies based on the information available, perceived risk and individual differences (Kazama & Watanuki, ; Kazama et al ., ). Some of these individual differences are stable, with consistently aggressive individuals reliably contributing intensively to group defence.…”
Section: Information For Predator Defencementioning
confidence: 99%